2009
DOI: 10.15871/1517-8595/rbpa.v11n2p129-136
|View full text |Cite
|
Sign up to set email alerts
|

Cinética De Secagem Em Camada Fina Da Banana Maçã Em Secador De Leito Fixo

Abstract: A cinética de secagem em leito fixo da banana maçã, fatiada em rodelas com espessuras de 5 a 10 mm e nas temperaturas de 50 a 70°C, e a aplicação de cinco modelos matemáticos, para a representação do processo de secagem, foi objeto de estudo do presente trabalho. Conforme os resultados obtidos, o processo de secagem ocorre totalmente à taxa decrescente e a variável temperatura tem maior influência. Os modelos que melhor representaram o processo de secagem foram o de Henderson e Pabis e o Exponencial 2 termos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
0
8
0
13
Order By: Relevance
“…The influence of increased dehydration temperatures in D eff was also found in investigations involving coconut bagasse (Jena and Das ) and banana (Silva et al . ): these researchers found that the diffusion coefficient was strongly influenced by temperature, in direct proportion.…”
Section: Resultsmentioning
confidence: 97%
“…The influence of increased dehydration temperatures in D eff was also found in investigations involving coconut bagasse (Jena and Das ) and banana (Silva et al . ): these researchers found that the diffusion coefficient was strongly influenced by temperature, in direct proportion.…”
Section: Resultsmentioning
confidence: 97%
“…A estimativa da umidade de equilíbrio é necessária para a avaliação da cinética de secagem, utilização dos modelos matemáticos e determinação da constante de secagem (k), difusividade efetiva de massa (D ef ) e energia de ativação (E a ) (Batista 2004, Silva et al 2009). …”
Section: Volumetric Contraction and Drying Kinetics Of Musa Sapientumunclassified
“…Thus, it requires mathematical models that represent the reduction in water content ratio of the products during the process (Alves, 2010). The use of mathematical models to represent the process is important, because the generated information is utilized in the development of devices and prediction of drying times (Silva et al, 2009). …”
Section: Introductionmentioning
confidence: 99%